Glycogen Synthase Kinase-3: A Promising Therapeutic Target for Fragile X Syndrome - Mines, Marjelo M.; Jope, Richard S. (Frontiers in Molecular Neuroscience, 2011)
Recent advances in understanding the pathophysiological mechanisms contributing to Fragile X Syndrome (FXS) have increased optimism that drug interventions can provide significant therapeutic benefits. FXS results from inadequate expression of functional fragile X mental retardation protein (FMRP). FMRP may have several functions, but it is most well-established as an RNA-binding protein that regulates translation, and it is by this mechanism that FMRP is capable of affecting numerous cellular processes by selectively regulating protein levels. The multiple cellular functions regulated by FMRP suggest that multiple interventions may be required for reversing the effects of deficient FMRP. Evidence that inhibitors of glycogen synthase kinase-3 (GSK3) may contribute to the therapeutic treatment of FXS is reviewed here. In the mouse model of FXS, which lacks FMRP expression (FX mice), GSK3 is hyperactive in several brain regions. Furthermore, significant improvements in several FX-related phenotypes have been obtained in FX mice following the administration of lithium, and in some case other GSK3 inhibitors. These responses include normalization of heightened audiogenic seizure susceptibility and of hyperactive locomotor behavior, enhancement of passive avoidance learning retention and of sociability behaviors, and corrections of macroorchidism, neuronal spine density, and neural plasticity measured electrophysiologically as long term depression. A pilot clinical trial of lithium in FXS patients also found improvements in several measures of behavior. Taken together, these findings indicate that lithium and other inhibitors of GSK3 are promising candidate therapeutic agents for treating FXS.